Literasi Digital Berbasis Sekolah Dalam Mencegah Tindakan Cyberbullying Pada Remaja - Saragih, Rasiana; Amini, Adillah Khaira; Jannah, Lizaida (Talenta Publisher, 2024)
Based on an APJII survey, which found that 49% of internet users admitted to having been bullied, ridiculed or harassed on social media. This survey also stated that as many as 31.6% of victims of bullying allowed the action, 7.9% retaliated, 5.2% deleted the teasing, while only 3.6% reported the action to the authorities (APJII , 2020). This research aims to determine the school's efforts to educate students to avoid behaviorcyberbulling as well as what literacy skills are given to students so that students are digitally skilled. Data collection was carried out through observation, interviews and documentation. From the research results, it is known that the school is trying to provide digital literacy knowledge to students by getting into the habit of reading books before the first lesson starts, providing advice between lessons and accompanying students if they are indicated to be cyberbullying at school. Keyword: Cyberbullying, Literacy, Digital, Teens